In Situ Capture of Bacterial Toxins for Antivirulence Vaccination. Issue 33 (28th June 2017) - Wei, Xiaoli; Gao, Jie; Wang, Fei; Ying, Man; Angsantikul, Pavimol; Kroll, Ashley V.; Zhou, Jiarong; Gao, Weiwei; Lu, Weiyue; Fang, Ronnie H.; Zhang, Liangfang
Abstract : Antivirulence vaccination is a promising strategy for addressing bacterial infection that focuses on removing the harmful toxins produced by bacteria. However, a major challenge for creating vaccines against biological toxins is that the vaccine potency is often limited by lack of antigenic breadth, as most formulations have focused on single antigens, while most bacteria secrete a plethora of toxins. Here, a facile approach for generating multiantigenic nanotoxoids for use as vaccines against pathogenic bacteria by leveraging the natural affinity of virulence factors for cellular membranes is reported. Specifically, multiple virulent toxins from bacterial protein secretions are concurrently and naturally entrapped using a membrane‐coated nanosponge construct. The resulting multivalent nanotoxoids are capable of delivering virulence factors together, are safe both in vitro and in vivo, and can elicit functional immunity capable of combating live bacterial infections in a mouse model. Despite containing the same bacterial antigens, the reported nanotoxoid formulation consistently outperforms a denatured protein preparation in all of the metrics studied, which underscores the utility of biomimetic nanoparticle‐based neutralization and delivery. Overall this strategy helps to address major hurdles in the design of antivirulence vaccines, enabling increased antigenic breadth while maintaining safety. Abstract : A nanotoxoid concurrently carrying multiple pathogen‐specific antigens is fabricated on‐demand by leveraging the interactions between naturally secreted bacterial virulence factors and cell‐membrane‐coated nanoparticles. The nanovaccine is confirmed to carry and neutralize known toxins from a model bacterium and is capable of significantly controlling bacteria growth when used to vaccinate mice. The reported approach may provide new avenues for controlling the rise of antibiotic‐resistant bacteria.